Preparation and Dissolution Characteristics of Sustained Release Diltiazem Hydrochloride Tablets (The East and Central African Journal of Pharmaceutical Sciences, 2018)
In the present study, the applicability of Eudragit to produce matrix tablet by a wet granulation technique was evaluated. The effect of various formulation variables on the release of drug from these tablets was examined. Release profiles of diltiazem hydrochloride were investigated using the rotating basket method described in the USP 24 with 1000 ml buffer solution (pH 1.2 and 6.8) maintained at 37 C. In vitro findings showed that matrix tablets prepared with Eudragit gave prolonged release of diltiazem hydrochloride. In order to understand the drug release mechanism better, the release data was tested assuming common kinetic models. In the present study, for the optimized formulation, the correlation coefficients were low for first order, zero order and Hixon-Crowell models. When the goodness of fit of release data to Matrix and Peppas equation was evaluated, the difference between these two models was found to be minimal. For the optimized formulation, the best-fit kinetic model was the Matrix model.
Keywords: Diltiazem hydrochloride; Matrix tablet; Sustained release; Eudragit; In vitro release studies.